Rediscovery and lectotypification of Scurrula stocksii (Loranthaceae): a rare and endemic species of Maharashtra, India - Chandore, Arun Nivrutti; Gosavi, Kumar Vinod Chhotupuri; Kambale, Sharad Suresh (Phytotaxa, 2023)
Scurrula stocksii (Hook.f.) Danser (Loranthaceae) is a rare parasitic plant species and restricted to the Maharashtra state of India. S. stocksii was described based on specimens collected by J.E. Stocks from Konkan region of Maharashtra. Cooke (1908) reported the species from Savantwadi area of Sindhudurg district of Konkan region of Maharashtra based on collection of Kanitkar. Mishra & Singh (2001) stated that in spite of intensive searching the species could not be traced in Sindhudurg district and might have been vanished from this district. While surveying Rajapur area of Ratnagiri District (Maharashtra), S. stocksii collected, therefore this collection represents the rediscovery after 127 years. Lectotype for Loranthus stocksii Hook.f. is designated here by ICN (Shenzhen code, 2018).